2011
DOI: 10.1021/cg200799n
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Morphology and Optical Properties of γ-BiB3O6Single Crystals

Abstract: High quality γ-BiB 3 O 6 single crystals up to 16 × 18 × 32 mm 3 in size were grown by the Kyropoulos technique. Indexes of the faces for as grown γ-BiB 3 O 6 single crystals were determined, and transmission spectra were recorded in polarized light. The band gap was found to be E g = 3.982, 3.968, and 4.008 eV at 300 K for E∥a, b, and c, respectively. E g decreases linearly versus temperature with a dE g /dT = 0.00127 eV/deg rate for E∥a as temperature grows from 80 to 300 K. Photoluminescence in the broad 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Since the discovery of a-BiB 3 O 6 in 1962, 17 considerable attention has been paid to the synthesis of new compounds from Bi 2 O 3 and B 2 O 3 components. [18][19][20][21][22][23] Up to now, four BiB 3 O 6 polymorphs have been identied, i.e. a-, b-, gand d-BiB 3 O 6 , where the aand d-BiB 3 O 6 crystals, belonging to monoclinic (C2) and orthorhombic (Pca2 1 ) crystal symmetries, respectively, were found to show noncentrosymmetric characteristics and exhibit stable temperature regions around 710-715 C and 680-710 C, respectively.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of a-BiB 3 O 6 in 1962, 17 considerable attention has been paid to the synthesis of new compounds from Bi 2 O 3 and B 2 O 3 components. [18][19][20][21][22][23] Up to now, four BiB 3 O 6 polymorphs have been identied, i.e. a-, b-, gand d-BiB 3 O 6 , where the aand d-BiB 3 O 6 crystals, belonging to monoclinic (C2) and orthorhombic (Pca2 1 ) crystal symmetries, respectively, were found to show noncentrosymmetric characteristics and exhibit stable temperature regions around 710-715 C and 680-710 C, respectively.…”
Section: A Introductionmentioning
confidence: 99%
“…23 In the past two decades, extensive studies have been carried out on the crystal growth, structure, and optical properties of aand d-BiB 3 O 6 crystals for nonlinear optical applications. [21][22][23][24][25][26] However, investigations of the electro-elastic properties for piezoelectric applications are very limited. 8,23 In this research, a-BiB 3 O 6 crystals were explored for piezoelectric sensor applications.…”
Section: A Introductionmentioning
confidence: 99%
“…The a phase crystallizes at temperatures above 710°C [10], while c phase is stable in temperature range 680-710°C [11]. Therefore single crystal growth of d-BIBO:Nd 3+ was carried out below 680°C from under-cooled melt containing 2 at% of Nd 3+ ions substituting for Bi 3+ ions.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the technological importance of α-BiB 3 O 6 , it is desirable to learn the chemistry behind these polymorphs. Therefore, remarkable studies were performed on the stability, crystal growth, physical properties, and phase relationship of the BiB 3 O 6 polymorphs. , A previous study on α-BiB 3 O 6 using variable-temperature neutron and X-ray diffraction (XRD) techniques on powder and single-crystalline samples revealed the anisotropic thermal behavior of this phase, but did not find any evidence of structural phase transformation to other polymorphs between 3.5 K and 999 K at ambient pressure . Recently, a detailed investigation of the phase transitions among the α-, β-, γ-, and δ-phases under different temperatures and pressures was reported .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high-pressure phase of δ-BiB 3 O 6 is stable below 670 °C at ambient pressure, and the stability field extends as the pressure increases. To date, all three of the thermodynamically stable phasesα-, γ- and δ-BiB 3 O 6 were grown as bulk crystals, using the top-seeded method at atmospheric pressure. ,, The measurements of the NLO coefficients on the δ-BiB 3 O 6 single crystal revealed that the largest d 33 value is 2.4 ± 0.4 pm/V, which is of the same order of magnitude as that of α-BiB 3 O 6 , and the transmission spectrum of the single crystal of γ-BiB 3 O 6 was recorded in a polarized light beam …”
Section: Introductionmentioning
confidence: 99%